Challenging Management of Pregnancy Complicated by Eisenmenger Syndrome; A Case Report - Kulsuma, Umme; Qumruzzaman, KH; Shameem, Md Kibria; Parveen, Tabassum; Islam, Nilufar; Wahid, Fatima; Afroj, Romena (University Heart Journal, 2025)
Women with diagnosed case of Eisenmenger syndrome are usually advised to avoid pregnancy because of high mortality rate 30% to 50%, which increase up to 65% in case of caesarean section. Literature survey showed, few case reports on successful pregnancy outcome with proper multidisciplinary approach in tertiary hospital those who wanted to continue pregnancy with informed written consent about high mortality rate patient with Eisenmenger syndrome who become pregnant are at a particular risk of rapidly progressive cardiopulmonary decompensation, thrombotic complications and sudden death2,3, because pregnancy related physiological changes are poorly tolerated in Eisenmenger syndrome. Prevention and early termination is advisable3,5. For patient who present in later stages of pregnancy, carefully coordinated multidisciplinary care involving experienced specialists from obstetrics, anesthesiology, cardiology, neonatology and critical care medicine is necessary to optimize the chances of survival for both mother and baby. We here present a case report of a 25- year -old 2nd gravida, P:1(VD-IUD) admitted in Fetomaternal medicine department, BSMMU with 36 weeks pregnancy with uncorrected ventricular septal defect(VSD), Eisenmenger syndrome, severe pulmonary hypertension ( 94mmHg), left ventricular dysfunction (EF-<39%), Fetal growth retardation (Wt-1600gm), oligohydramnios (AFI-5.6cm), Gestational diabetes mellitus (on diet) with Hypothyroidism. By meticulous multidisciplinary approach Caesarean section done and shifted to Coronary care unit (CCU). She delivered a growth restricted (birth wt1500gm) male baby with Apgar score: 8 and managed in Neonatal care unit (NICU). University Heart Journal 2024; 20(1): 36-39